Biological properties of Cucurbita maxima extracts - How, Fiona Ni Foong; R., Ahmad M.; Arief Ichwan, Solachuddin Jauhari (Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Peel, pulp and seeds of Cucurbita maxima were extracted from aqueous (water) and phosphate buffered saline (PBS) at incubated temperature of 37 deg C similar to normal human physiological temperature to investigate the potential of these extracts as antibacterial agents and cytotoxic agents using antibacterial susceptibility assay against six pathogenic bacteria of gram positive and negative and cytotoxic assay against Human non-small cell lung carcinoma cell line (H1299). The phytochemical contents of all the extracts were determined to correlate with their biological properties.